INDEKS BAHAYA EROSI (IBE) PADA BEBERAPA PENGGUNAAN LAHAN DI DESA MALEI KECAMATAN BALAESANG - Nurmani, Anthon Monde, Abdul Rahman, Usman (AGROTEKBIS, 2016)
This study aims to determine Erosion Danger Index (IBE) on multiple use of land in the village Malei. This research was conducted in the village of Malei, District Balaesang Tanjung, Donggala and Soil Science Laboratory, Faculty of Agriculture, University of Tadulako. This research was conducted in October 2014 to January 2015. This study used survey methods, primary and secondary data collection, implementation of research in the form of preparation, research and data processing. Analysis of existing data is done by using the USLE (Universal Soil Loss Equation) equation A = RKLSCP and erosion are allowed (T), using the equation Erosion Danger Index IBE = A / T. The results showed that generally palm plantations, cloves, and nutmeg has a value of Erosion Danger Index (IBE) moderate (> 1) 1.6 up to 3.56, except on land with a slope clove 0 -15% have values that IBE Low and forest lands 0.007 to 0.04.